Evaluating the role of MRI with diffusion-weighted images in diagnosis of uterine focal lesions - Hoda A.E Abd Elsamie; Mahmoud I El-Rasheedy; Mohammed A.A Mohammed (Wolters Kluwer Medknow Publications, 2019)
Objective The aim of this study is to highlight the role of MRI with diffusion-weighted (DW) images in diagnosis of uterine focal lesions, especially in differentiation between benign and malignant masses, and initial staging of known malignancies. Patients and methods A total of 34 patients with uterine focal lesion were included in the study. The patients' age ranged from 25 to 87 years old, with mean age of 49.6 years. All the patients were referred from the Obstetrics and Gynecology Department to Radiodiagnosis Department at Al Azhar Assiut University Hospital during the period from November 2017 to October 2018. Results In this study, DW MRI could correctly diagnose 33 of 34 lesions. It correctly diagnosed 22 of 22 benign lesions (facilitate diffusion) and 11 of 12 malignant lesions. Overall, 11 malignant lesion showed restricted diffusion, and only one malignant lesion showed facilitated diffusion. Conclusion This study suggests that, in addition to conventional MRI features, DW imaging provided an additional tool for distinguishing uterine benign focal lesions from malignant lesions.